Why are some countries more productive? A study of the impact of capital market misallocation on productivity in both developed and developing countries - Yuan, Zihan (2014)
Why do some countries produce so much more than others? One popular explanation is that capital market distortions lower the aggregate productivity of a country by allocating resources ine ciently. This paper follows the generalized average revenue product (ARP) approach, which incorporates heterogeneities in output and demand elasticity into the existing ARP model. Applying the method to rm-level datasets from 31 countries, together with Penn World Table that includes information about country level aggregate total factor productivity (TFP), we nd that there is indeed a signi cant negative relationship between aggregate TFP and measure of capital misallocation across countries.